Implementasi Peraturan Larangan Merokok di Jalan Raya Kota Batam Ditinjau dari Perspektif Hukum Normatif - Permatasari, Rika; Rachmadhanto, Dimas Adam Satrio; Anjawai, Namrysilia Buti; Simanjuntak, Fhlorida Agustina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The prohibition of smoking in public spaces is a legal policy aimed at protecting the public’s right to a clean and healthy environment. Local governments have enacted regulations on smoke-free areas as a measure to control the negative impacts of tobacco use, including in open public spaces such as public roads. This study aims to analyze the implementation of regulations prohibiting smoking on public roads in Batam from a normative legal perspective. The research employs a normative legal research method using statutory and conceptual approaches. The legal materials analyzed consist of legislation, legal literature, and legal doctrines related to health law and law enforcement. The results indicate that the regulation on smoking prohibition is supported by a strong and hierarchical legal framework; however, its implementation has not been fully effective. This is due to weak law enforcement, inadequate application of sanctions, and low public compliance with the existing legal norms. Therefore, strengthening legal substance and ensuring consistent enforcement are necessary to enhance the effectiveness of smoking prohibition on public roads.